DATING SIMULATOR IN INDONESIA - Dominikus Reynard Darmawan (Soegijapranata Catholic University, 2015)
Japanese culture has been entering Indonesia, especially anime, fashion, and dating sim. How big the effect of the existence of dating sim in Indonesia?